Rancang Bangun Six Step Inverter untuk Motor Brushless Direct Current Outrunner pada Sepeda Listrik - Maskur, Muhammad Ali; Qudsi, Ony Asrarul; Ferdiansyah, Indra (Majalah Ilmiah Teknologi Elektro; Vol 23 No 1 (2024): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2024.v23i01.P03, 2024)
In general, BLDC motors have a position sensor (hall sensor) in them, where there is a hall sensor, this will provide position information feedback to the observer so that by using the sensored method the motor operation can be carried out properly because the control is perfectly synchronized with the rotor position. This research discusses regulating the speed of a brushless DC motor using a BLDC inverter motor control method, namely six-step commutation. This system uses a modified folding bicycle concept, with the controller coming from a microcontroller integrated with an Android application to monitor measurement data. Tests were carried out partially and integrated the entire system without load and using mechanical loads. The test results in this research are that the three-phase inverter has an error rate of 0.75%, as well as the voltage sensor which has an error rate of 0.49%, and the current sensor with an error rate of 0.994%. The motor speed produced by the inverter will increase as the input voltage increases. The maximum speed that an electric bicycle can reach is 30 km/h. Battery voltage, current and power measurement data is sent in real time to the Android application. Keyword— BLDC Motor, Three-Phase Inverter, Six-Step Commutation, Hall Sensor, Electric Bicycle